Development of a Multi-Standard Protocol Using Software Defined Radio for a Mobile Station Transceiver - Mohamed Osman, Khalid Eltahir (2009)
In this thesis, the Software Defined Radio Digital Control System (SDR DCS) has been developed to perform a multi-standard protocol of the handset using the GSM and CDMA systems. The SDR DCS was designed for the SDR based band digital transceiver of the handset as a control and protocol software to control and handle the operation of the handset when roaming between different protocols; it could easily and quickly let the handset reconfigure with the future protocol; it configured the handset with either of the GSM or CDMA protocol software, and scheduled for reconfiguration of the handset with the second protocol in sequence. The SDR DCS controls the download of the specific air interface environment. In order to implement the whole design in software, the design had to go through three stages. The first stage was to do all the design steps in the software using generic computing resources such as Hardware Description Language (HDL), with the top-level design for each protocol. The second stage was to define a logic circuit to perform the signal processing for each protocol; this step was applied after the simulation and synthesis, and eventually programming that circuit into the FPGA board. The third stage was to use the FPGA to implement the functions required for each protocol which constitutes the multi-standard protocol. The VHDL files were created for each element of the GSM and CDMA protocols. The GSM related system was developed with encoders and decoders linked to the channel model. The CDMA related system was designed with a transmitter to encode the user’s data into wide bandwidth using a reverse link channel and a synchronized receiver to receive the signal from the forward link channel and decode the wide bandwidth to recover the base band user’s data. The Synopsys™ software package was used for the design, synthesis and simulation of the SDR base band platform. The simulation tools used include the Model Sim and System Studio. Meanwhile, the Xilinx ISE 9.2i was used as the synthesis tool. The results of the simulated and synthesized top-level design files were downloaded into the Xilinx XSA-3S1000 FPGA board. The waveforms for the GSM and CDMA outputs approximately matched the ones seen in the oscilloscope for the FPGA output pin. This proved that the SDR DCS had successfully implemented its task, according to the objectives of the design.